2013
DOI: 10.1039/c3sm50183c
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale mechanics of wood cell walls under axial strain

Abstract: Trees and other woody plants are hierarchically structured to achieve a wide range of mechanical properties-necessary for their survival under various and varying loading conditions-with a narrow range of chemical composition. The hierarchical level understood to be directly responsible for modulating the longitudinal elastic modulus and yielding behavior is that of the composition of the cell walls, which consists of crystalline cellulose fibrils embedded in an amorphous matrix of hemicellulose and lignin. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 46 publications
(119 reference statements)
0
60
0
Order By: Relevance
“…The anisotropic behaviour of the cell walls in lignocellulosic material (wood) has been investigated by Qing and Mishnaevsky (2009a) using a finite element model, whereas experimental work was performed by Burgert (2006). On the other hand, the cellulose-hemicellulose interface has recently been investigated numerically by Adler and Buehler (2013), where they suggested a stick-slip motion of the interface. In addition, Qing and Mishnaevsky (2009b) and Flores and Friswell (2012) modelled cellulose as a cylindrical material surrounded by lignin and hemicellulose.…”
Section: D Micromechanical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The anisotropic behaviour of the cell walls in lignocellulosic material (wood) has been investigated by Qing and Mishnaevsky (2009a) using a finite element model, whereas experimental work was performed by Burgert (2006). On the other hand, the cellulose-hemicellulose interface has recently been investigated numerically by Adler and Buehler (2013), where they suggested a stick-slip motion of the interface. In addition, Qing and Mishnaevsky (2009b) and Flores and Friswell (2012) modelled cellulose as a cylindrical material surrounded by lignin and hemicellulose.…”
Section: D Micromechanical Modelmentioning
confidence: 99%
“…However, it should be noted that pre-treatment of lignocellulosic fibres like OPEFB can cause degradation of the fibre components, namely cellulose, hemicellulose, and lignin (Isroi et al 2012). This we believe can cause significant damage to the fibres as the lignin and hemicellulose bind the cellulose fibrils together and provide structural integrity to the lignocellulosic fibres (Adler and Buehler 2013). Note that for OPEFB, it was reported that the composition of cellulose, hemicellulose, and lignin are 47.6%, 28.1%, and 13.1%, respectively Omar et al (2014).…”
Section: D Micromechanical Modelmentioning
confidence: 99%
“…In Figure 4A-G, the EDS mapping results show homogeneous chemical element distribution in the steel and CSCB. 43 Figure 8B showed the average peak flexure stress of E1, E2, and CSCB with adding 0, 10, and 13% glass fibers as function of temperature. The transition zone for the adhesion interface between the steel substrate and CSCB was about 15 nm, due mainly to the rough, inclined steel/CSCB interface.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 The specimens were tested under a variety of loads at different annealing temperatures. 43,44 The specimens were tested under a variety of loads at different annealing temperatures.…”
Section: Microindentation Testmentioning
confidence: 99%
“…In previous MD simulations of PP, the degree of polymerization indicating the number of monomers in a single chain is chosen to be 100, which leads to a chain contour length of around 30 nm . In the CG polymer model, the bond length between neighboring CG beads is selected as 1 nm, which is similar to those used in previous studies of the CG modeling of polymer materials, such as collagen, cellulose, hemicellulose, and epoxy . For the crystalline cellulose molecule, it consists of the un‐branched chains, which are formed by the covalently linked glucose molecules .…”
Section: Methodsmentioning
confidence: 99%